Analysis of service quality on train passenger's perception by applying fuzzy topsis method - Gama Magistra Piche; Hendri Andi Mesta (Universitas Negeri Padang, 2021)
This study will only focus on the external side of the company, namely from the perspective of passengers who use transportation services from PT. Kereta Api Indonesia Divre II West Sumatra for the Padang-pariman route. In this study, the population size is unknown. Thus, determining the sample size of the population using the theory developed from Isaac Michael. The method of data collection in this study is observation, interviews, and questionnaires. In this study, researchers used the servqual method and fuzzy topsis ranking to measure service quality. The results of research on the quality of service in the West Sumatra Regional Division II train are from the five criteria studied by the researchers, namely, tangible, reliability, responsiveness, assurance, and empathy, there is the highest gap value on the responsivenesses criteria, namely the preference value of 0.9587, and the next is the tangible criteria. It was concluded that there are several criteria that have met the quality of service, namely the responsiveness criteria where passengers assess the response of train staff to what passengers need while at the station or train is good, as well as for tangible criteria, passengers feel the facilities on the train are able to satisfy train passengers. Meanwhile, the quality of service in the security or assurance department is considered by passengers to be normal. And for reliability and empathy, passengers rate about service qualities on these two criteria still not satisfying passenger.